The Indonesian Restorative Justice Application during Covid-19 Pandemic - Irsyad Dhahri Samad; Risma Niswaty; Badaruddin Badaru; Mochdar Yanlua (Seminar Nasional LP2M UNM, 2022)
Abstract. Since the first Covid-19 case was reported in March of 2020, the development of the Corona Virus Disease 2019 (Covid-19) pandemic in Indonesia has experienced active cases with the death rate graph dynamically increasing. Various efforts were continuously made within the Indonesian legal system, including how to protect the people who become victims of social stigma and discrimination in line with diagnosed and misdiagnosed Covid-19 sufferers. Covid-19 sufferers used to be burdened with humiliation, outcast, and disrespect occurred within the family or local community making them victims for restorative application. As stigma and discrimination had victimized into psychological effects and social conditions, McCold’s suggestion of restorative application known as the Primary Stakeholder, explains losses recovery. Using the theory, Indonesian Legal System has responded, however limited to cases of minor crimes, women dealing with law, children, and narcotics. Keywords: Covid-19; Indonesia; McCold; Restorative justice; victims